Development of Automatic Badminton Playing Robot with Distance Image Sensor. Issue 8 (2019) - Mizuno, Naoki; Makishima, Takuya; Tsuge, Kenta; Kondo, Sho; Nonome, Tomoaki; Kurebayashi, Hideaki; Otake, Shota; Shibata, Daichi; Yamakawa, Satoko
Abstract: We developed a full automatic badminton playing robot "MRO Brothers". The developed robot can receive and serve in the same environment as human badminton player. In this system, the shuttle is detected by Kinect sensor and its orbit is estimated based on the distance image of the shuttle. Moreover, the robot can automatically move to the spot where a shuttle will fall and hit it back by normal badminton racket.